A description of the Madagascar Teal Anas bernieri and an examination of its relationships with the Grey Teal A. gracilis - Young, H Glyn; Sorenson, Michael D; Johnson, Kevin P (Wildfowl, 1997)
The Madagascar Teal is one of the least known of all ducks. Recent studies, and the capture of live adults for a captive breeding programme, have allowed the first accurate description of the species and analysis of morphological and genetic relationships with its closest relative, the Grey Teal.